If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-2y+1)=2y-1
We move all terms to the left:
-(-2y+1)-(2y-1)=0
We get rid of parentheses
2y-2y-1+1=0
We add all the numbers together, and all the variables
=0
y=0/1
y=0
| 9a-4+3(a-11=23 | | 100/60=(4/5)/x | | 23x=23,000 | | 13x+2=100 | | 2+4(6-2x)=8 | | 0.75x=63.75 | | 2x+85+5x+29=93 | | 13m=300 | | 4(3b+7)=88 | | 1.6^(x-4)=5^(3x) | | -2(7z-4)=50 | | 4(7-6k)=-28 | | -2/1j=7/8 | | 2x^2+31x-7.9=0 | | 6.3a+15=90.6 | | -3(4n-5)=24 | | 3(6+5w)=18 | | (2/1)x+13=9 | | 2x-11=x-15=2x-72 | | 20/100=x/75 | | 0=16t^2+8 | | 2x-x=48 | | 8=9m-4m=3 | | -26p-6(5-6p)=6(p-5)-32 | | 2(-3+6z)=42 | | x=0.18x+24.41 | | x=0.18x+24.41 | | 2/5=y+4/3y | | 4x÷7=3 | | -1.5+k=8.2k=8.2+(-1.5)k=6.7 | | (x-3/7)=2/3(3x/2-9/14) | | -5(4f+3)=65 |